Enhanced rotator cuff tendon-bone interface regeneration with injectable manganese-based mesoporous silica nanoparticle-loaded dual crosslinked hydrogels - Chen, Zihang; Liu, Youjie; Liang, Tianxiang; Du, Zhaoyuan; Deng, Liming; Wu, Zhiwen; Li, Ye; Zhong, Haobo; Ma, JinJin; Li, Riwang; Wang, Huajun; Dong, Qiu; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionDuring the healing process, the functional gradient attachment of the rotator cuff (RC) tendon-bone interface fails to regenerate, which severely impedes load transfer and stress dissipation, thereby increasing the risk of retears. As a result, the treatment of rotator cuff tears remains a significant clinical challenge.MethodsIn this study, a dual-crosslinked hyaluronic acid/polyethylene glycol (HA/PEG) hydrogel scaffold was synthesized using hyaluronic acid and polyethylene glycol as base materials. Manganese-doped mesoporous silica nanoparticles (Mn-MSN) were incorporated into the hydrogel system to fabricate a manganese-based mesoporous silica nanoparticle-loaded dual-crosslinked hydrogel (Mn-MSN@Gel). The physicochemical properties of Mn-MSN@Gel, including porosity, elemental distribution, mechanical properties, biodegradability, and biocompatibility, were systematically characterized. The ion release profiles of Si4+ and Mn4+ were evaluated to assess sustained delivery. Rheological properties and self-healing capabilities were examined to determine injectability and in vivo stability. In vitro, the effects of Mn-MSN@Gel on cell migration, proliferation, and differentiation were assessed using rat bone marrow mesenchymal stem cells (rat-BMSCs) and tendon-derived stem cells (rat-TDSCs). The expression of osteogenic, tenogenic, oxidative stress-related, and inflammatory cytokine genes was analyzed. In vivo, a rat rotator cuff repair model was established to evaluate the biomechanical properties and tissue regeneration at the tendon-bone interface (TBI) following Mn-MSN@Gel injection.ResultsCharacterization demonstrated that Mn-MSN@Gel possesses a porous three-dimensional structure with uniform distribution of silicon, oxygen, and manganese elements, enabling sustained and slow release of Si4+ and Mn4+ ions. Additionally, the composite material exhibited excellent mechanical properties, biodegradability, and biocompatibility, while promoting cell migration/proliferation and accelerating regeneration of the tendon-bone interface. Mn-MSN@Gel enhanced the expression of osteogenic differentiation genes (Runx2, Alp, Sox9) in rat-BMSCs, upregulated tenogenic differentiation markers (Scx, Tnmd, Col3a1), and downregulated Mmp3 expression in rat-TDSCs. Furthermore, Mn-MSN@Gel modulated genes related to oxidative stress (Nrf2, Gpx4, Sod2) and inflammatory cytokines (IL-6, IL-10, Tnf-α), exhibiting anti-inflammatory effects and alleviating oxidative stress damage. In the rat rotator cuff repair model, Mn-MSN@Gel injection significantly improved postoperative biomechanical properties and promoted tissue regeneration at the TBI.DiscussionThe self-healing and injectable properties of Mn-MSN@Gel ensure precise delivery and stable integration in vivo. By combining mechanical support with sustained release of bioactive ions, Mn-MSN@Gel provides a comprehensive therapeutic strategy for regenerative repair of the tendon-bone interface. Its biocompatibility and bioactivity facilitate cell recruitment, migration, and lineage-specific differentiation, which are crucial for reconstructing the functional gradient structure of the TBI. The anti-inflammatory and antioxidant effects further contribute to a favorable healing microenvironment. Overall, these findings indicate that Mn-MSN@Gel is a foundational biomaterial with significant therapeutic potential for enhancing structural regeneration and functional recovery of the TBI following rotator cuff injury.